ANALYSIS OF HUMAN RESOURCE MANAGEMENT STRATEGY IN A STATE OF WAR AT AN ENTERPRISE - ZHOSAN, Hanna; DOBRIANSKYI, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the conditions of the modern world, where geopolitical conflicts and threats of war remain relevant, the issues of effective personnel management at enterprises during martial law become so important that they require extraordinary attention and research. In the context of such extraordinary circumstances, the management of human resources acquires new challenges and features that require careful analysis and development of strategies aimed at ensuring the functioning of enterprises in the wartime period. The analysis of the personnel management strategy of the enterprise in the conditions of martial law becomes an urgent task, which requires the study of various aspects of the impact of military conflicts on organizational culture, employee motivation, security and sustainability of the enterprise. In this context, the research and analysis of personnel management strategies become a scientific and practical task that can make a significant contribution to maintaining the stability and competitiveness of enterprises in the extraordinary circumstances of a military conflict.The problem lies in the need to analyze and develop an optimal personnel management strategy at the enterprise under martial law conditions, taking into account the extraordinary circumstances, threats and limitations that arise in such situations.The article conducts an analysis of personnel management strategies for enterprises in conditions of wartime. A detailed examination of the impact of military conflict on the operations of enterprises and their personnel is carried out, including the identification of threats, limitations, and extraordinary circumstances. The article also discusses various personnel management strategies that can be employed to ensure stability and productivity during times of war. The authors provide a comprehensive table of strategies, their areas of application, characteristics, and drawbacks. Based on the analysis, practical recommendations are offered to enterprises for adapting and optimizing personnel management strategies in wartime conditions with the aim of ensuring their survival and successful operation in extraordinary circumstances.
Keywords: Personnel Management; Wartime Conditions; Strategy Analysis; Enterprise Survival; Impact of Military Conflict; Personnel Strategy Optimization; Extraordinary Circumstances